Detecting and drilling in critical inclination window in slant wells by means of a two phase liquid-solid CFD model and experimental study - Dehvedar, Mohsen; Moarefvand, Parviz (Kuwait Journal of Science, 2019)
Build and hold from vertical section form slant wells. The hole cleaning phenomena in this wells can cause of many problems that increased the operational costs. CFD simulation and experimental flow loops are good devices for studying the effect of operational parameters on cutting transport across the annulus. In this study tried to build a liquid-solid CFD model that verified with experimental data. The effect of cutting size, drill pipe rotation speed, flow rate, drilling fluid type and rate of penetration were discussed. The results indicated that there is a specific critical inclination window for slant wells and the driller must avoid to drill in it. The inclinations between 30 to 55 degrees form this window. If there is no way to drill in this period, the operator must increase the flow rate as possible and tried to reduce the size of the cuttings with different ways. Increasing the drilling fluid viscosity also improved the hole cleaning efficiency.